ACCEPTANCE AND SHELF LIFE OF PATIN NUGGET (Pangasius sp.) FORTIFIED WITH MORINGA LEAF FLOUR (Moringa oleifera) - Naomi Magdalena Simatupang; Syahrul Syahrul; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTMoringa leaves are leaves that have good nutritional content, Moringa leaves have been scientifically proven to be a source of nutraceuticals in amounts that exceed other plants.Fortification is an effort to improve the nutritional quality of food (food) by adding one or more certain micronutrients to the food. The purpose of this study was to determine the level of consumer acceptance, the best treatment and also changes in the quality of catfish nuggets fortified with moringa leaf flour in cold storage (50C).. The research method used is an exploratory method, namely conducting experiments for fortification of Moringa leaf flour in processing catfish nuggets using four treatments, namely without Moringa leaf flour (0%), Moringa leaf flour (1%), Moringa leaf flour (3%)  and Moringa leaf flour (5%), then each treatment was tested using an organoleptic test and the results were tested descriptively. The results showed that the second treatment was the best formulation and after being tested on the product for 14 days got the best results on day 7, with organoleptic values of appearance (3,68), aroma (3,76), taste (3,6), texture (3,28), water content 50,51 %, total plate number 3,2 x 104 colonies/g and total volatile base nitrogen (TVB N) 0,84 N mg/100 gr. The results of the tests carried out on catfish nuggets fortified Moringa leaf flour have met the quality requirements of fish nuggets according to SNI 7758:2013.Keywords ; cold storage, fish nuggets, moringa leaves, fortification.